2008
DOI: 10.1590/s0100-879x2008000800009
|View full text |Cite
|
Sign up to set email alerts
|

Reduced folate carrier 1 (RFC1) is associated with cleft of the lip only

Abstract: In this report, we have reanalyzed genotyping data in a collection of families from South America based on maternal origin. Genotyping analysis was performed at the Craniofacial Anomalies Research Center at the University of Iowa. These genotypes were derived from genomic DNA samples obtained from blood spots from children born with isolated orofacial clefts in 45 hospitals located in eight countries (Argentina, Bolivia, Brazil, Chile, Ecuador, Paraguay, Uruguay, and Venezuela) collaborating with ECLAMC (Latin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 38 publications
0
12
0
3
Order By: Relevance
“…Investigating genetic variations that influence cellular absorption, transport, and metabolism of folic acid may offer insights into the role of this vitamin on NSCL/ P pathogenesis. Previous investigations of genes that are involved with folic acid metabolism, including 5,10-methylenetetrahydrofolate reductase (MTHFR), methylenetetrahydrofolate dehydrogenase 1 (MTHFD1), 5-methyltetrahydrofolate-homocysteine methyltransferase (MTR), and solute carrier family 19-member 1 (SLC19A1), have demonstrated an association of functional polymorphisms with increased maternal risk of NSCL/P (Shotelersuk et al, 2003;Mostowska et al, 2006;Mills et al, 2008;Vieira et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Investigating genetic variations that influence cellular absorption, transport, and metabolism of folic acid may offer insights into the role of this vitamin on NSCL/ P pathogenesis. Previous investigations of genes that are involved with folic acid metabolism, including 5,10-methylenetetrahydrofolate reductase (MTHFR), methylenetetrahydrofolate dehydrogenase 1 (MTHFD1), 5-methyltetrahydrofolate-homocysteine methyltransferase (MTR), and solute carrier family 19-member 1 (SLC19A1), have demonstrated an association of functional polymorphisms with increased maternal risk of NSCL/P (Shotelersuk et al, 2003;Mostowska et al, 2006;Mills et al, 2008;Vieira et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The aim of the current report was to assess the possible role of MTHFR c.677C>T in the expression of NSCL/P phenotype in a Chilean population, based on two complementary stages: a case–control study (stage 1) and a case–parent trio study (stage 2). We have considered as reference the results of two previous studies from the ECLAMC including lower number of OFC Chilean subjects and analyzed jointly with other samples from South American countries (Vieira et al , , ). Both reports did not show association between MTHFR c.677C>T and non‐syndromic OFCs.…”
Section: Discussionmentioning
confidence: 99%
“…The aim of this study was to evaluate the possible role of MTHFR c.677C>T in the expression of NSCL/P in the Chilean population. As reference, the literature shows two previous studies including Chilean OFC subjects and their mothers from the Latin American Collaborative Study of Congenital Malformations (ECLAMC) (Vieira et al , , ). In these reports, Chilean samples were grouped with other South American subjects and no associations between this variant and OFCs were detected.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, this study is the first to stratify the results of genotyping based on mtDNA haplotypes in Europeans. Initial work performed using data based on South American individuals suggested that association with specific genes is detected only when data are stratified by mtDNA haplotype (22, 23). It is unlikely that mtDNA variants play a direct role in the development of CL/CLP.…”
Section: Discussionmentioning
confidence: 99%